A giant cell tumour of distal end of the tibia: a rare case report - Govindarajan, Lakshman Prasath; Panchanathan, Nedunthuraikoe; Saminathan, Udhayaprakash (International Journal of Research in Medical Sciences, 2023)
A tumor that is locally aggressive is a giant cell tumor (GCT). The distal end of the femur, proximal end of the tibia, distal end of the radius, and proximal humerus are common locations. Presenting the case of a 52-year-old man who has a giant cell tumor in the unusual position of the lower end of the right tibia. Patient came with complaints of pain and swelling in the right ankle. The tissue’s histopathology reveals spindle-shaped mononuclear cells suggestive of GCT and multinucleated giant cells with homogenous vesicular nuclei. Curettage and bone cement were used to treat the patient and fill the defect.